Biomarkers of Endothelial Damage and Disease Severity in COVID-19 Patients - Panagiota Tsiatsiou; Dimitrios Pilalas; Vasiliki Tsaireli; Antonia Lanta; Georgios Meletis; Angeliki Kassomenaki; Evangelia Tza; Lampros Tampakas; Helen Gkeka; Maria Papaioannou; Efthymia Protonotariou; Lemonia Skoura (Current Issues in Molecular Biology)
The severe outbreak of SARS-CoV-2, the etiological agent of COVID-19, has precipitated the development of vaccines and antiviral therapeutics. However, it remains a significant public health concern. This study investigated the association between disease severity, biomarkers of coagulation, and endothelial damage, including P-selectin, thrombomodulin, PAI, von Willebrand antigen (VWF: Ag) and von Willebrand factor ristocetin cofactor (VWF: RCo). A cross-sectional, observational study was conducted in a cohort of 90 adult COVID-19 patients (≥18 years), categorized into three groups: ICU-hospitalized, non-ICU hospitalized, and asymptomatic non-hospitalized (outpatient). In these groups, biomarkers, including PAI-1, TM, and P-selectin, were assessed using enzyme-linked immunosorbent assay (ELISA), and immunological assays for VWF: Ag and VWF: RCo. Across all groups, we observed significantly elevated levels of P-selectin, VWF: Ag, and VWF: RCo. Elevated levels of PAI-1 and TM were observed in ICU patients compared to non-ICU and asymptomatic patients, indicating increased endothelial injury and activation. Furthermore, COVID-19 mutations significantly affect the P-selectin biomarker. This finding supports the hypothesis that P-selectin is a more reliable biomarker for assessing the severity of the disease than other endothelial damage and coagulation markers, especially in heterogeneous clinical presentations. Our study also highlights the requirement of comprehensive examination for its broader implications in viral strains, infection severity, and genetic variants.